The Influence of Grandparents on Children’s Diets - Roberts, M.; Pettigrew, Simone (Journal of Research for Consumers, 2010)
Grandparents play an important role in feeding their grandchildren, yet the families in this qualitative study reported that grandparents usually provide their children with unhealthy food. Grandparents were frequently discussed as one of the major enablers of children’s unhealthy eating, yet they remain overlooked in campaigns to improve children’s diets. The findings suggest ways that social marketers can develop specific campaigns to improve children’s diets through their grandparents.